PERFORMANCE OPTIMIZATION STRATEGIES OF SHARIA INSURANCE COMPANIES IN INDONESIA BASED ON ASSET GROWTH (2018-2022) - Faradifa, Nurul; Takidah, Erika; Ulupui, I Gusti Ketut Agung (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
A good performance description of Sharia insurance companies is reflected in their asset growth rate; when the generated percentage increases, it represents the company's optimal performance in managing participants' funds, thereby enhancing public trust and encouraging more people to register as Sharia insurance participants. This study aims to examine the relationship between Insurance Claims, Profitability, and Operational Expenses on Asset Growth by involving 27 Sharia insurance companies registered with the Financial Services Authority from 2018 to 2022 as research samples. The sample was drawn using the Purposive Sampling technique and quantitative methods with secondary data obtained from the annual financial statements of each Sharia insurance company's website. The partial results show that claims and operational expenses have a significant negative impact on asset growth; the higher the claims and operational expenses, the lower the asset growth. Profitability, however, does not affect asset growth because the profitability generated is not optimal, thus not increasing the company's assets. Simultaneously, claims, profitability, and operational expenses have a significant positive effect on asset growth, with a determination coefficient of 40.09%, while the remaining percentage is influenced by other factors not examined in this study. Therefore, this study adds value by validating the measurement of asset growth in Sharia insurance.